Festas e devoções marianas em Manaus, Itacoatiara e Manacapuru, Amazonas: catolicismo popular e vida urbana - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This thesis presents an anthropological look about the popular devotion to The Virgin Mary in three cities of the Amazonas State. Each of these cities recognizes The Virgin Mary as their “patron saint” with different denominations: Our Lady Nazareth, in Manacapuru City; Our Lady of Rosario, in Itacoatiara City; and Our Lady Immaculate Conception, in Manaus. The Catholicism presence and manifestation on Amazon lands were observed from the belief and practice of the faithful, who articulate Iberian Catholicism elements as well as local mythical narratives present in the Amazonian imaginary. We sought to relate historical and ethnographic aspects about the promotion of the cult and the celebrations to The Virgin Mary in the Amazon, by taking practices of the traditional and popular Catholicism in the midst of the urban and social transformations of the studied cities.
Keywords: Virgem Maria; Catolicismo na Amazônia; Virgin Mary; Catholicism in Amazon; CIÊNCIAS HUMANAS: ANTROPOLOGIA: ANTROPOLOGIA URBANA